Effect of resisted exercise on autonomic cardiac modulation in elderly women: STROBE-compliant study. Issue 10 (11th March 2022) - Isidoro, Naerton José Xavier; Oliveira, Fernando Rocha; Raimundo, Rodrigo Daminello
Abstract : Abstract: Heart rate variability (HRV) is an important cardiac health marker, with lower values indicating a reduction in vagal control of cardiac rhythm and decreasing significantly with advancing age. In this study, we evaluated the effects of strength exercises for the upper and lower limbs on cardiac autonomic modulation in elderly women. We registered 29 participants using a portable RS800CX heart rate monitor to record the RR intervals. For the collection of HRV data, the volunteers remained seated at rest for 10 minutes. After the rest period, the participants performed the exercises. Immediately after the exercise protocol, the subjects remained seated at rest for 30 minutes. HRV indices were analyzed in the following periods: rest, 0 to 10 minutes, 5 to 10 minutes, 10 to 20 minutes, and 20 to 30 minutes. Systolic arterial pressure and diastolic arterial pressure were measured in the following periods: rest, immediately after exercise, and 30 minutes after exercise. Regarding the mean of the RR intervals, heart rate, and indexes of the time and frequency domains surveyed, there were no statistically significant differences between the 4 moments in the protocols for upper and lower limbs. No significant differences were found in systolic and diastolic pressures between the 3 time points surveyed in the protocols for the upper and lower limbs. Resistance exercises performed with low-intensity loads and a greater number of repetitions did not promote significant variations in cardiac autonomic modulation and blood pressure levels, showing good safety in elderly women.